Comparison of quantitative real‐time PCR and short‐term (18‐hour) microculture in diagnosis of fetal cytomegalovirus infection: Impact of hyperimmunoglobulin treatment. (7th September 2018) - Penka, Lukas; Kagan, Karl‐Oliver; Goelz, Rangmar; Hamprecht, Klaus
Abstract: Objective: The prognostic value of human cytomegalovirus detection (HCMV) DNA levels from amniotic fluid (AF) for the outcome of the infected newborn is still a matter of debate, especially if the onset of maternal primary infection at amniocentesis is unknown. The objective of this study was to investigate the analytical performance in short‐term (18‐hour) microculture from preconcentrated samples and quantitative real‐time PCR (rtPCR) for diagnosis of fetal HCMV infection. Methods: A retrospective diagnostic study was conducted on 51 AF samples taken from women that transmitted HCMV prenatally. Amniocentesis was performed around 22‐week gestation. The samples were tested for HCMV viral load via quantitative rtPCR and additionally with quantitative short‐term (18‐hour) microculture following preconcentration via a 50 000 g centrifugation step prior to inoculation to fibroblast monolayers. Results: Both methods show correlating results ( ρ  = 0.903). In 25 samples, the women received intravenous hyperimmunoglobulin prior to amniocentesis resulting in a lower correlation of both quantitative methods ( ρ  = 0.445), in reduced median copy numbers of HCMV DNA ( P  = .037) and reduced viral infectivity in short‐term microculture ( P  = .025). Conclusion: Both methods lead to correlating results using AF samples from HIG‐naïve women. Human cytomegalovirus viral load and infectivity in cell culture are reduced in samples following maternal hyperimmunoglobulin treatment. Abstract : What's already known about this topic? Human cytomegalovirus detection (HCMV) via quantitative real‐time PCR and short‐term (18‐hour) microculture in amniotic fluid determine foetal HCMV infection. Discordant results concerning the role of HCMV viral load (VL) leading to symptomatic HCMV infection after birth are discussed. What does this study add? Both methods show correlating results; correlation diminishes after maternal treatment with hyperimmunoglobulin (HIG). Maternal HIG therapy disproportionately influences microculture results compared to PCR